2019
DOI: 10.1080/10717544.2019.1650849
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular administration of tetramethylpyrazine hydrochloride to rats: a direct delivery pathway for brain targeting?

Abstract: The purpose of this study was to compare the pharmacokinetic profile of tetramethylpyrazine hydrochloride (TMPH) in rat plasma and tissues following intravenous (iv), intragastric (ig) and intraocular (io) administration. After io, ig and iv administration of a single dose at 10 mg/kg, tissue and plasma samples drawn from the femoral artery were collected at timed intervals. The concentration of TMPH in the samples was analyzed using high-performance liquid chromatography (HPLC). The area under the concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Previous research has demonstrated that ligustrazine has the ability to penetrate the BBB and distribute across various brain regions ( Tsai and Liang, 2001 ). However, its biological half-life when taken orally is limited to 0.5–2 h. Utilizing ligustrazine - loaded liposomes ( Xia et al, 2016 ), transdermal administration drugs ( Qi et al, 2002 ), intranasal administration ( Feng et al, 2009 ), and intraocular administration ( Mao et al, 2019 ) can enhance the efficiency of ligustrazine in crossing the BBB and reaching the brain. Moreover, ligustrazine exhibits protective effects against CIS damage by reducing BBB permeability ( Tan et al, 2015 ; Jin et al, 2021 ), possibly through the inhibition of the JAK/STAT signaling pathway ( Gong et al, 2019 ) and the reduction of MMP-9 levels ( Jin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that ligustrazine has the ability to penetrate the BBB and distribute across various brain regions ( Tsai and Liang, 2001 ). However, its biological half-life when taken orally is limited to 0.5–2 h. Utilizing ligustrazine - loaded liposomes ( Xia et al, 2016 ), transdermal administration drugs ( Qi et al, 2002 ), intranasal administration ( Feng et al, 2009 ), and intraocular administration ( Mao et al, 2019 ) can enhance the efficiency of ligustrazine in crossing the BBB and reaching the brain. Moreover, ligustrazine exhibits protective effects against CIS damage by reducing BBB permeability ( Tan et al, 2015 ; Jin et al, 2021 ), possibly through the inhibition of the JAK/STAT signaling pathway ( Gong et al, 2019 ) and the reduction of MMP-9 levels ( Jin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%